Quantitative Analysis of the Innominate Bone for Sex Estimation Utilising the Phenice Method - Muhammad Naqib Harith Hamzah; Siti Hanum Mohd Ali; Faridah Mohd Nor; Helmi Hadi (Springer Open, 2024)
Indexed by WOS/Scopus